(untitled) (Fiep Bulletin - online, 2025)
In the contemporary scenario, understanding the complex interactions between the body and the mind has been a constantly expanding field of research. Among the areas of interest is Attention Deficit Hyperactivity Disorder (ADHD), a neuropsychiatric condition that mainly affects children and often persists into adulthood. This research aimed to analyze the influence of Physical Education classes on children with ADHD. This is a descriptive study, classified as field research. The population was composed of school teachers, and the sample was made up of three teachers who work with children with ADHD. A questionnaire developed by the researchers in charge was used. The data collected were tabulated using Microsoft Office Excel 2007. The results showed that physical activity at school contributes to the improvement of children with ADHD. It was concluded that regular physical exercise during physical education classes has a positive impact on the physical and cognitive development of children with ADHD.